A Status Hukum Wali yang Dianggap Mafqud Bagi Anak yang Orang Tuanya Bercerai: (Studi kasus di Kantor Urusan Agama Kecamatan Gudo) - Zahro, Ahmad; Khotim, Ahmad; Abdur Rohman, Ahmad Aminuddin (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. Requests for a guardian judge due to the guardian's nasab mafqud often occur with children whose parents are divorced, often found when a divorce occurs, one of the parents does not get custody of their child, does not care about their obligations to their child, as if they have disappeared without giving any news, especially visiting. to provide a living, and his whereabouts are unknown after the separation of the child's parents' relationship. Which ultimately makes it difficult for the child to carry out the marriage because the guardian is hampered by mafqud. Aim. This research aims to understand the implementation process of determining guardian judges as a result of mafqud in the Gudo Religious Affairs Office and how the proof of guardian mafqud carried out by the Gudo District KUA is viewed from an Islamic legal perspective and a positive legal perspective. Methods. This type of research is field research which is descriptive in nature using a phenomenological approach. Primary data sources were obtained through interviews and documentation from Gudo District KUA officials and supported by secondary data in the form of written literature or scientific works. Results. The results of this research explain that in determining the guardian of the judge because the guardian of the nasab is mafqud, the KUA officials refer to the procedures contained in Minister of Religion Regulation Number 20 of 2019. However, in proving the guardian of mafqud only with the testimony of the village head and there is no need for a judge's decision, in this case there is a lack of synchronization with the laws and regulations. -Existing invitations in Indonesia need to be improved.